Evaluating and upgrading the performance of a bridge network structure with Rayleigh distribution lifetimes. - Hossam A Nabwey; Adel A El-Faheem; Mohammed Ashraf Denguir; A M Rashad (PLoS ONE)
In this work, bridge network model with Rayleigh distribution lifetimes is used. Two main techniques are calculated to upgrade this model: reduction and redundancy techniques. In order to compare the effectiveness of the various approaches, the survival function, the mean time to failure and gamma-fractiles for the original and upgraded model are calculated. Finally, we analyze comprehensively a computer simulation example to distingue between the methods. The numerical simulations were done in Mathematica which indicated that the upgraded system performs better than the original one and the best technique is by cold duplication.